Komposisi Kimia Pupuk Kompos dari Limbah Padat Rumah Potong Hewan Tamangapa Kota Makassar - Hartono Hartono; Surahman Nur; Oslan Jumadi (Fakultas MIPA UNM, 2022)
Abstract. Slaughterhouses (RPH) produce large amounts of solid waste every day and have not been utilized optimally. RPH solid waste has great potential to be used as plant fertilizer through the composting process. Composting is expected to change the organic material composition of the abattoir solid waste to be more ideal to support plant growth. This study aims to determine the chemical composition of compost made from waste at RPH Tamangapa Makassar City before and after the composting process. Composting from solid waste at Tamangapa RPH Makassar was carried out using the main ingredients, namely rumen contents (treatment I) and rumen contents mixed with livestock manure in a ratio of 1:1 (Treatment II). The composting process was carried out in a compost box with a size of 40x40x60 cm with a passive aeration system for 4 weeks with three replications. Quantitative data tested in this study included the content of N-total (%), C-Organic (%), P-total (%), K-total (%), C/N ratio, organic matter (%), water content (%) and compost reduction (%). The results showed that the content of elements C, N, P, K, C/N ratio, organic matter, and water content before composting in both treatment I and treatment II were generally still low and almost the same as the raw materials. After the composting process took place, the content of C, P, K, C/N ratios generally showed an increase, while the N content was relatively constant. The results of the analysis showed that there was no significant difference between the chemical composition of the compost in the treatment and both before and after the composting process.Keywords: RPH solid waste, composting process, chemical composition of compost, C/N ratio.